Spontaneous Non-Traumatic Intracranial Hemorrhage In Pre-Existing Hypertensive Patient - An Autopsy-Based Case Report (Journal of Forensic Medicine & Toxicology, 2026)
In north- eastern states high intake of salt and social acceptance for the use of tobacco lead to hypertension, atheroscle rosis and development of renal stones which ultimately increases chances for the intra-cerebral hemorrhage. Intracranial hemorrhage or stroke is one the leading cause of premature deaths in northeastern states. A 54year old male deceased, was brought with history of scuffle. On clinical examination, MRI showed intraparenchymal bleed of size approximately 18 x 49 x 65 mm in right hemisphere and extending up to midbrain and pons. History of scuffle was ruled out on metic ulous post-mortem examination by confirming findings of MRI with findings of intra-ventricular hematoma and liq uefactive necrosis was present at midbrain and pons region. This study explored non-traumatic brain hemorrhage as a cause of death in sudden and unexpected deaths without any prior evidence of any significant illnesses which could easily have been misinterpreted as trauma to head. It has been evident that hypertension in north-eastern population is higher due to lifestyle and food-habits. To the best of our knowledge, an Autopsy based study on Non-traumatic Intracranial Haemorrhage has not yet been published from North – Eastern region of India.
Keywords: Spontaneous intracranial hemorrhage; Hypertension; Renal stone; Non-traumatic